A Generalized Analytical Solution for Preferential Infiltration and Wetting. Issue 1 (28th February 2019) - Stewart, Ryan D.
Abstract : Core Ideas: New model simulates relative infiltration and wetting depth due to preferential flow. Solution normalizes parameters to account for soil properties and initial conditions. Preferential flow estimations match closely with dual‐permeability HYDRUS‐1D results. Preferential flow wetting depths decrease as volume of macropore domains increase. Model provides new insight into preferential flow dynamics during rainfall events. Macropores induce preferential flow in many soils, creating the need for parsimonious solutions to describe nonequilibrium infiltration and wetting processes. This study applied the Green–Ampt infiltration model within a dual‐domain framework to distinguish water movement through the soil matrix vs. through macropores. Using a nondimensional parameter set to generalize the results, the developed equations enabled estimates of infiltration and depth of wetting due to preferential flow during constant‐intensity rain. The analysis revealed that infiltration partitioning varies with time, with flow regimes changing at time of ponding of the matrix and again at time of ponding in the macropores. The results also showed that the fraction of infiltration due to preferential flow increases as a function of rainfall and relative volume of the macropore domain. Conversely, macropore volume has an inverse relationship with wetting depth: all other factors being equal, infiltration due to preferential flow becomes proportionally greater than matrix infiltration as macropore volume decreases. Finally, the proposed infiltration and wetting equations were compared with numerical simulations of the Richards equation for dual‐permeability soils. The analytical solutions closely approximated the numerical results, with root mean square deviation values ≤0.15 and simulated wetting depths within 35% of one another, even as modeled times to ponding varied by 5 to 80%. Altogether, the theoretical framework developed in this study provides new insight into preferential flow dynamics during rainfall events.